Legal Analysis of the Regency/City Election of The Watchdog Authority in Handling the Violations of the Code of Ethics for the Sub District General Election Committee of Ad Hoc - Ilmanbahri Widyananda Mansyur; Andi Pangerang Moenta; Muh. Hasrul (IHSA Institute, 2021)
This research aims to analyze the authority had by the general election supervisory agency of regency/city in handling violations of the code of ethics for the sub-district general election supervisory committee and outlines the ideal concepts of handling violations of the code of ethics for the sub-district general election supervisory committee. This research used normative legal research method which examined and resolved legal issues done by analyzing the legal materials was primary legal materials and secondary legal materials. Those legal materials were then analyzed using a statutory, historical, comparative and conceptual approach in order to resolved the legal issues examined and drew conclusions on researched legal issues.This research’ results show that: 1. The implementation of the authority of the regency/city election of the general election supervisory agency in the process of handling violations of the election supervisory committee of Ad Hoc has been carried out in the 2019 election, However, it was just that the implementation has not been considered effective inasmuch as there have been still several factors that hindered its implementation, such as the legal factor itself, the lack of harmony in regulations related to the implementation of handling authority. Then, the institutional factor, institutionally the general election supervisory agency of the regency/city that has hierarchical relationship with the election supervisory committee of Ad Hoc, and the third factor related to the high number of the violators of the code of ethics of the election supervisory committee of Ad Hoc in all over Indonesia, 113 cases of which 102 were proven and 11 were not proven; 2. In the process of handling the violations of the code of ethics, the sub-district general election supervisory committee should have been formed of election organizer ethics council on an Ad Hoc basis to examine Ad Hoc election organizers with 1 person of the general election commission, 1 person for the element of election supervisory agency and 1 person from community that the aspects of the audit authority were examined openly and presented both sides based on the principle of audi et alterm partem.